A Survey of Family Planning Training, Knowledge, and Practices Among Health Care Providers Within the Military Health System at Joint Base Lewis–McChord. Issue 5 (25th September 2018) - Deans, Elizabeth I; Batig, Alison L; Cordes, Sarah; Scribner, Alicia N; Nielsen, Peter E; Jamieson, Denise J; Lathrop, Eva; Cwiak, Carrie
Abstract: Introduction: Within the active duty U.S. military population, the age-adjusted unintended pregnancy rate is higher than the national average. Unplanned pregnancy within the military impacts individual and unit medical readiness. Contraceptive education and availability are means to reduce unintended pregnancy rates; health care providers are key facilitators in provision of contraception. Understanding provider knowledge and practices related to contraceptive provision may identify strengths and gaps in order to provide focal points for sustainment or improvement in family planning practices. The purpose of this study was to assess family planning knowledge, training, and practices among health care providers serving military and dependent beneficiaries within the military health care system at Fort Lewis, Washington. Material and Methods: This was a cross-sectional survey of health care providers on Joint Base Lewis–McChord in Tacoma, Washington who deliver health care services to U.S. uniformed service members and their dependents in varied settings, including outpatient clinics and a tertiary care center. The survey included questions regarding prior contraceptive training, and current contraceptive knowledge and practices. Survey results were evaluated using descriptive and bivariate analyses. The study was approved by both Institutional Review Boards at Emory University and at Madigan Army Medical Center. Results: Overall, 79 eligible health care providers completed the survey. Eighty-six percent of women's health providers consistently ("always or most of the time") provided family planning services to female service members, compared with 38% of primary care providers. Women's health providers were more likely to counsel by method effectiveness and adapt their counseling to consider patients' reproductive life plans. There were no differences between provider type in considering service members' deployment status during contraceptive counseling. Overall, providers identified the correct effectiveness of long-acting contraceptive methods, but tended to overestimate the effectiveness of short-acting methods. Conclusions: Family planning services available to service members may be improved through enhanced provider education, targeting efficacy-based counseling and identification of barriers to access and provision of long-acting reversible contraceptive methods.